2017
DOI: 10.24071/ijiet.2017.010209
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Learning Autonomy Through the Implementation of Flipped Learning in Language Teaching Media Course

Abstract: Dealing with millennial generations, it is essential that educators adjust the educational paradigm in order to adapt to the needs of students in the digital age as it is today. This research studied about the implementation of flipped classroom learning model in Language Teaching Media (LTM) to foster fifth semester students' learning autonomy in English Teacher Education Study Program, Sanata Dharma University. Through the implementation of flipped classroom using Learning Management System (LMS), it is expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 2 publications
3
18
0
Order By: Relevance
“…Purnama (2017, p. 1) mentions that "By highlighting youths' characteristics that tend to be visual and addicted to rapid information, memes and Instagram may be used as one of the strategies to develop an innovative teaching and learning process." It is in line with Wulandari (2017) who suggests that flipped classroom in digital environment gives positive learning atmosphere. Although the meaning of engagement may be the same both in online learning activities and in conventional classroom, it might be different in challenges (see Isworo, 2016, p. 12) and barriers.…”
Section: Introductionsupporting
confidence: 71%
“…Purnama (2017, p. 1) mentions that "By highlighting youths' characteristics that tend to be visual and addicted to rapid information, memes and Instagram may be used as one of the strategies to develop an innovative teaching and learning process." It is in line with Wulandari (2017) who suggests that flipped classroom in digital environment gives positive learning atmosphere. Although the meaning of engagement may be the same both in online learning activities and in conventional classroom, it might be different in challenges (see Isworo, 2016, p. 12) and barriers.…”
Section: Introductionsupporting
confidence: 71%
“…The use of technology in an Indonesian context fosters learner autonomy, reduces anxiety, and improves critical thinking skills (Pasaribu, 2016;Pasaribu & Iswandari, 2019;Prasetyawati & Ardi, 2018;Wulandari, 2017). Seeing the advantages of using technology in the classroom, EFL teacher candidates in the English Language Education Study Program are strongly encouraged to take CALL, a course offered for the English Language Education Study Program.…”
Section: Computer Assisted Language Learning (Call)mentioning
confidence: 99%
“…I am sure that the information is more complete in the reading materials. (FGD_R4) From the text in bold, it was revealed that the students show behavioral engagement in terms of reading the materials outside the class in advance of class meetings (Basal, 2015;Webb, Doman, & Pusey, 2014;Wulandari, 2017). F7 suggests that the students think being able to prepare for the materials before the class is ideal.…”
Section: Flipping the Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also improved student performance after introduction of the flipped classroom [18][19][20][21]. Previous research has also shown that after participating in the flipped class, students reported that they had 'enjoyed' the class, were 'actively participating,' had 'autonomy in learning,' and experienced an increase in their 'motivation to learn' [22,23].…”
Section: Introductionmentioning
confidence: 99%